Respiratory Severity Score and Neurodevelopmental Outcomes at Age 3 Years in Extremely Preterm Infants - Tamai, Kei; Takeuchi, Akihito; Nakamura, Makoto; Matsumoto, Naomi; Yorifuji, Takashi; Kageyama, Misao (American Journal of Perinatology, 2024)
Objective We aimed to examine the association between respiratory severity score (RSS; mean airway pressure × fraction of inspired oxygen) and neurodevelopmental outcomes in extremely preterm infants.Study Design This was a single-center, retrospective cohort study. We analyzed data from extremely preterm infants who were admitted to the neonatal intensive care unit at Okayama Medical Center between 2010 and 2019. Infants without invasive respiratory management during the first day of life were excluded. The exposure variable was the highest RSS during the first day of life. RSS was categorized into two groups: low (<3.5) and high (≥3.5) RSS. The primary outcome was death or neurodevelopmental impairment at age 3 years, defined as cognitive impairment (developmental quotient <70) or the presence of cerebral palsy. Secondary outcomes were the components of the primary outcome. We conducted robust Poisson regression analyses to investigate the association between RSS category and primary and secondary outcomes, adjusting for perinatal confounders.Results The cohort included 97 infants with neurodevelopmental data, of whom 34 and 63 infants were in the low- and high-RSS categories, respectively. The median (interquartile range) gestational age and birth weight were 26.0 (24.7–26.9) and 25.7 (24.6–26.7) weeks and 761 (584–866) and 806 (618–898) g for infants in the low- and high-RSS categories, respectively. Compared with infants in the low-RSS category, those in the high-RSS category had a greater risk of death or neurodevelopmental impairment at age 3 years (26.3 vs. 42.3%; adjusted risk ratio [RR], 2.0; 95% confidence interval [CI], 1.1–3.5) and neurodevelopmental impairment at age 3 years (17.6 vs. 28.6%; adjusted RR, 2.7; 95% CI, 1.3–5.9).Conclusion High RSS (≥3.5) during the first day of life was associated with an increased risk of neurodevelopmental impairment at age 3 years in extremely preterm infants.Key Points
Keywords: respiratory severity score; neurodevelopment; extremely preterm; mortality; cerebral palsy